Catalytic liquefaction of municipal sewage sludge over transition metal catalysts in ethanol-water co-solvent. (February 2018) - Wang, Wenjia; Yu, Qi; Meng, Han; Han, Wei; Li, Jie; Zhang, Jinglai
Highlights: Municipal sewage sludge was 97.74% liquefied with CuSO4 in ethanol-water co-solvent. CuSO4 reduced the content of N and S in biocrude by 14.6% and 55.0%, respectively. Appropriate conditions concentrated more C and H in biocrude. More light-oil contents and esters were in biocrude with CuSO4 catalyst. Abstract: Catalytic liquefaction of (Municipal sewage sludge) MSS over transition metal catalysts in ethanol-water co-solvent (EWCS) was investigated. The effect of operating parameters like temperature, holding time, and ethanol-water ratio was discussed. CuSO4 was selected as the most efficient catalyst. The highest biocrude yield (47.45%) and liquefaction conversion (97.74%) was both obtained at the same conditions following: a reaction temperature of 270 °C, a holding time of 30 min, an ethanol-water ratio of 1:1, and with CuSO4 as the catalyst. Optimized operating conditions reduced Sulfur and Nitrogen content in biocrude by 55.0% and 14.6%, respectively. The obtained biocrude samples were analyzed and characterized by thermogravimetric analysis (TGA) and gas chromatography-mass spectroscopy (GC-MS), which suggested that adding CuSO4 increased the light-oil like content in biocrude and more than 60% of compounds in biocrude were esters. This process demonstrates the effectiveness of catalytic liquefaction of MSS in EWCS over CuSO4 catalyst.